Sex, lies and butterflies [videorecording (DVD)] - Giamatti, Paul (Nature (Television program), 2018)
Butterflies have been flying around the planet for over 50 million years, and today around 20,000 different species inhabit the globe. From egg to caterpillar to chrysalis to the winged insect, this follow their life stages, highlighting their survival techniques and the new science that is unlocking the secrets of their world and changing the view of these fantastic and yet fragile creatures.